ANTIMICROBIAL RESISTANCE PATTERNS IN COMMUNITY ACQUIRED URINARY TRACT INFECTIONS - Gilani, Syed Yasir Hussain; Shah, Syed Raza Ali; Ahmad, Nasir; Bibi, Saima (Journal of Ayub Medical College Abbottabad, 2016)
Background: Urinary tract infection (UTI) is the most frequent disease for which patients seek medical care. The antimicrobial agents causing UTI and their sensitivity patterns have remarkably changed throughout the world over the past few years. Hence, the present study was designed to explore the uropathogens and their susceptibility to various molecules in our region. Methods: This descriptive cross sectional study was conducted at Medical C Unit of Ayub Teaching Hospital, Abbottabad from January 2015 to January 2016. Patients with clinical features of UTI were evaluated using Urine R/E and Urine culture and sensitivity. Ten antibiotics were checked for susceptibility. Results were analysed using SPSS 17. Results: A total of 630 patients presented with urinary complaints. Of these, 236 patients had more than 8-10 pus cells on urine R/E. They were further evaluated using culture and sensitivity and positive culture was obtained in 75 patients. Of these 34 (45.3%) were males and 41 (54.7%) were females. E Coli was the predominant isolate being present in 49 (65.3%) patients. This was followed by Klebsiella in 9 (12%) patients. Tazobactam-piperacillin and cefoperazone-sulbactam were the most sensitive drugs having overall sensitivity of 96% and 93.3% respectively. The isolates were highly resistant to Fluoroquinolones 77.3% followed by Penicillins 72% and TMP-SMX 69.3%.Conclusion: Antibiotic sensitivity patterns have enormously changed over the past decade. Newer agents are quite efficacious but their use should be highly judicious to prevent the development of resistance to these molecules. Keywords: Urinary tract infection; sensitivity; resistance; antimicrobials